Pentraxin-3 vs C-reactive protein and other prognostic biomarkers in acute coronary syndrome: A substudy of the Platelet Inhibition and Patients Outcomes (PLATO) trial. Issue 4 (1st June 2020) - Kontny, Frederic; Andersen, Thomas; Ueland, Thor; Åkerblom, Axel; Lakic, Tatevik G; Michelsen, Annika E; Aukrust, Pål; Bertilsson, Maria; Becker, Richard C; Himmelmann, Anders; James, Stefan K; Siegbahn, Agneta; et al.
Abstract : Aims: We investigated the dynamics, associations with patient characteristics, other biomarkers, and clinical outcomes of pentraxin 3 in acute coronary syndrome. Methods and results: In multivariate analyses, pentraxin 3 measured in 5154 patients randomised in the Platelet Inhibition and Patients Outcomes (PLATO) trial (NCT00391872) was compared with leukocytes, high-sensitivity C-reactive protein, interleukin-6, cystatin C, N-terminal prohormone brain natriuretic peptide, high-sensitivity troponin T and growth differentiation factor 15 concerning prediction of clinical outcome. Pentraxin 3 peaked earlier than high-sensitivity C-reactive protein and was more strongly correlated with N-terminal prohormone brain natriuretic peptide and high-sensitivity troponin T than with high-sensitivity C-reactive protein. The frequency of cardiovascular death, spontaneous myocardial infarction or stroke by quartiles of pentraxin 3 at admission was 6.1%, 7.3%, 9.7% and 10.7%, respectively ( p <0.0001). The hazard ratio per 50% increase of pentraxin 3 was 1.13 (95% confidence interval: 1.07–1.19), p <0.0001. This association remained significant after stepwise adjustments for leukocytes/high-sensitivity C-reactive protein (1.09 (1.02–1.15)), p =0.009, interleukin-6 (1.07 (1.01–1.14)), p =0.026, and cystatin C (1.07 (1.00–1.13)), p =0.044, but not after adjustment for N-terminal prohormone brain natriuretic peptide, high-sensitivity troponin T and growth differentiation factor 15. Admission pentraxin 3 was also associated with several of the individual endpoint components (cardiovascular death/spontaneous myocardial infarction; p =0.008, cardiovascular death; p =0.026, and spontaneous myocardial infarction; p =0.017), but not with stroke. Pentraxin 3 measured in the chronic phase (i.e. at one month) was still predictive of the composite endpoint in univariate analysis (1.12 (1.04–1.20) per 50% increase) p =0.0024, but not after adjustment for the other biomarkers. Conclusion: Admission level of pentraxin 3 is a modestly stronger predictor than high-sensitivity C-reactive protein and interleukin-6, but not than N-terminal prohormone brain natriuretic peptide or high-sensitivity troponin T, concerning cardiovascular outcome in acute coronary syndrome. Pentraxin 3 is more strongly correlated with N-terminal prohormone brain natriuretic peptide and high-sensitivity troponin T than with high-sensitivity C-reactive protein.